ATIM-31. SAFETY OF TUMOR-SPECIFIC PEPTIDE VACCINE TARGETING ISOCITRATE DEHYDROGENASE 1 MUTATION IN RECURRENT RESECTABLE LOW GRADE GLIOMA PATIENTS. (11th November 2019) - Peters, Katherine; Congdon, Kendra; Archer, Gary; Woodring, Sarah; Jaggers, Denise; Lipp, Eric; Healy, Patrick; Herndon, James; Soher, Brian; Vlahovic, Gordana; Johnson, Margaret; Randazzo, Dina; et al.
Abstract: BACKGROUND: Low grade gliomas (LGGs) represent 10–15% of glial tumors in adults and while LGG patients have a better prognosis over high-grade gliomas, these cancers ultimately recur and transform to more aggressive tumors. Isocitrate dehydrogenase 1 (IDH1) is commonly mutated in LGG, and when mutated, it is the oncogenic driver by leading to the production of oncometabolite 2-hydroxyglutarate (2-HG). We developed a phase 1 study for recurrent resectable IDH1 mutant LGG utilizing a tumor-specific peptide vaccine targeting IDH1 mutant protein that spans the mutated region of IDHR132H (PEPIDH1M vaccine). METHODS: We performed a phase 1, single-center, clinical trial in recurrent resectable IDH1 mutant WHO grade II glioma patients. Subjects received three PEPIDH1M vaccine q2wks and then proceeded to surgical resection. If subject's tumor retained grade II status, then the subject proceeded with 12 cycles of daily TMZ (50 mg/m2 X 28 days) and PEPIDH1M vaccine (12 injections q4wks). If subject's tumor transformed to grade III, then subject proceeded to radiation therapy (RT) with concurrent TMZ followed by 12 cycles of daily TMZ (50 mg/m2 X 28 days) and PEPIDH1M vaccine (12 injections q4wks). Primary endpoint was safety of PEPIDH1M vaccine in combination with adjuvant TMZ and/or XRT/TMZ and evaluable subjects needed to receive ≥6 PEPIDH1M vaccines. We assessed safety using CTCAE 4.03. RESULTS: We enrolled 24 recurrent LGG subjects with mean age of 43.8 yrs (sd=11.4 yrs). Twenty subjects completed ≥6 PEPIDH1M vaccines. Most common related toxicity was grade 1 injection site reaction (N=20) and skin induration (n=17) with no grade 3–4 related toxicities. CONCLUSIONS: PEPIDH1M vaccine in combination with surgical resection, daily TMZ and/or RT + TMZ with daily TMZ was safe and well tolerated in recurrent IDH1 mutant LGG. We are currently exploring secondary/correlative endpoints including immunogenicity of PEPIDH1M vaccine and magnetic resonance spectroscopy for 2-HG.